A generalized proximal-point method for convex optimization problems in Hilbert spaces. (3rd October 2017) - Kanzow, Christian; Steck, Daniel
Abstract: We deal with a generalization of the proximal-point method and the closely related Tikhonov regularization method for convex optimization problems. The prime motivation behind this is the well-known connection between the classical proximal-point and augmented Lagrangian methods, and the emergence of modified augmented Lagrangian methods in recent years. Our discussion includes a formal proof of a corresponding connection between the generalized proximal-point method and the modified augmented Lagrange approach in infinite dimensions. Several examples and counterexamples illustrate the convergence properties of the generalized proximal-point method and indicate that the corresponding assumptions are sharp.